A comprehensive review study of cyber-attacks and cyber security; Emerging trends and recent developments. (November 2021) - Li, Yuchong; Liu, Qinghui
Abstract: At present, most of the economic, commercial, cultural, social and governmental activities and interactions of countries, at all levels, including individuals, non-governmental organizations and government and governmental institutions, are carried out in cyberspace. Recently, many private companies and government organizations around the world are facing the problem of cyber-attacks and the danger of wireless communication technologies. Today's world is highly dependent on electronic technology, and protecting this data from cyber-attacks is a challenging issue. The purpose of cyber-attacks is to harm companies financially. In some other cases, cyber-attacks can have military or political purposes. Some of these damages are: PC viruses, knowledge breaks, data distribution service (DDS) and other assault vectors. To this end, various organizations use various solutions to prevent damage caused by cyber-attacks. Cyber security follows real-time information on the latest IT data. So far, various methods had been proposed by researchers around the world to prevent cyber-attacks or reduce the damage caused by them. Some of the methods are in the operational phase and others are in the study phase. The aim of this study is to survey and comprehensively review the standard advances presented in the field of cyber security and to investigate the challenges, weaknesses and strengths of the proposed methods. Different types of new descendant attacks are considered in details. Standard security frameworks are discussed with the history and early-generation cyber-security methods. In addition, emerging trends and recent developments of cyber security and security threats and challenges are presented. It is expected that the comprehensive review study presented for IT and cyber security researchers will be useful.